Physical and anatomical features and drying behavior of the boards produced from old date palm trees (Phoenix dactylifera L.) in Bam city - Tarmian, Asghar; Foroozan, Zeynab; Sepehr, Amir; Gholamiyan, Hadi; Oladi, Reza (Iranian Journal of Natural Resources, 2013)
In this study, the physical and anatomical properties of old date palm wood (Phoenix dactylifera L.) and its drying behavior was studied. Four old date palm trees grown in Bam city (Kerman provenience) were felled. Then, boards with the dimension of 300 × 50 × 30 mm were cut at DBH of trees from pith to bark. After measuring the green moisture content and specific gravity, boards were dried in a semi-industrial kiln to reach the final moisture content of 8% using a mild wood drying schedule. Cross-sectional anatomical measurements were performed on the nearest boards to the bark and pith. Results showed that the green moisture content and specific gravity of date palm wood ranged between 150-260% and 0.29–0.39 and the moisture content was increased and the specific gravity was decreased from pith to bark. Anatomical observations and statistical analysis revealed that there was no statistically significant difference between the average number of vessel elements and vessel bundles between pith and bark, but the mean vessel area in pith was considerably greater than bark. Results also showed that the drying rate of date palm wood was high reaching the final moisture content of 8% within 7 days. The drying rate of bark samples was higher than those of the pith and no deformation and surface crack was observed in the dried board
Keywords: Date palm; Drying; Physical properties; Anatomy